A split face comparative study between intradermal tranexamic acid and Erbium-YAG laser in treatment of melasma. (2nd January 2022) - Otb, Sarah; Shaarawy, Eman; Sadek, Ahmad; Abdallah, Noha; Agamia, Naglaa; Soliman, Mona; Tawfik, Abeer Attia
Abstract: Background: Although there are different treatment modalities of melasma, it remains a challenging problem. Erbium-YAG laser proved its efficacy in melasma improvement with minimal downtime. Tranexamic acid (TA) is a new promising treatment of melasma Objective: The first objective is to compare between the efficacy of intradermal injection of TA and Erbium-YAG laser in the treatment of melasma. The second objective is to use the dermoscope as an objective evaluation method. Patients and methods: A split face study was conducted on 28 patients. One side of the face received intradermal TA injection. The other side was treated with laser. Melasma Area and Severity Index (MASI) and the dermoscope were used for evaluation of treatment. Results: The MASI scores showed a significant decrease in TA treated side. The dermoscope assessment showed no significant difference in both treatment modalities. Conclusion: A promising results were obtained by both intradermal TA and Erbium:YAG laser; however, the TA yields a higher patient satisfaction because of its high efficiency and low cost.